Indian Media in Global Context. Issue 4 (April 2016) - Rajagopal, Arvind
Abstract: There is a curious partitioning of media histories of the west from those of other countries. The kind of comparative analysis that would be expected with a set of global technologies and practices is lacking. Although communications media were promoted as a technology of nation building by western powers and received as such by countries such as India, strangely, there is a wide gap between the rhetoric of globality and the literature pertaining to local and national uses of media technologies. My essay situates the history of post‐independence media growth in India within this gap, in a preliminary attempt to bridge it.